Measuring the purpose in life in the adult population: A scoping review - Arunjit, Somrudee; Balthip, Karnsunaphat; Latour, Jos M. (Belitung Raya Foundation, Indonesia, 2024)
Background: The purpose in life can motivate individuals to realize that life is essential for existence and well-being. Adults might experience crises that can lead to a lack of purpose in life. Consequently, promoting purpose in life is necessary, but it requires a suitable measurement scale. Objective: This scoping review aimed to identify and map the content, psychometric properties, and answer option scales of instruments intended to measure purpose in life in adult populations. Design: A scoping review was employed. Data Sources: The database used was PubMed. The libraries were APA PsycNet, Wiley Online Library, and Cochrane Library. The search strategy was performed between 1 November 2023 and 14 February 2024. Review Methods: This review used the scoping review framework described by Arksey and O’Malley. The identified instruments were assessed for quality based on the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) criteria. This study also used the PRISMA Extension for Scoping Reviews (PRISMA-ScR) reporting guideline. Results: A total of 348 studies were identified, and seven articles were involved in the final synthesis. These seven articles included five instruments measuring the concept of purpose in life, of which two instruments had two versions: 1) Purpose in Life Test (20 items, 4 items); 2) Life Engagement Test (6 items); 3) Psychological Well-Being (120 items, 18 items); 4) Self-Assessment Goal Achievement (9 items); and 5) National Institutes of Health Tuberculosis Meaning and Purpose Scale Age 18+ (18 items). The validity of all instruments was tested using factor analysis, known groups, face, concurrent, convergent, discriminant, and construct validity. The reliability of four instruments was tested by Cronbach’s alpha and Spearman-Brown formula. Conclusion: Five instruments measuring purpose in life in the adult population with adequate psychometric properties were identified. The clinical implication of this study suggests that nurses may consider employing an appropriate instrument to assess the purpose of life in the adult population, thus enabling them to offer holistic, individualized care to adults, particularly addressing the spiritual dimension.